2018
DOI: 10.1002/star.201700273
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Potato Starch‐Based Nanocomposites: Development, Characterization, and Biodegradability

Abstract: The primary objective of this study is to develop and characterize a novel active biodegradable nanocomposite film using sweet potato starch (SPS) for food packaging. Montmorillonite (MMT) nanoclay at a constant weight of 3% and thyme essential oil (TEO) at three levels (2%, 4%, and 6% v/v) are incorporated into SPS film. The results show that incorporating MMT and TEO into SPS film greatly enhanced (P < 0.05) water resistance by 50%. MMT incorporation also hinders the degradation rate of the film. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 26 publications
(30 reference statements)
0
22
0
1
Order By: Relevance
“…These findings indicate that the incorporation of TEO significantly increases the yellowness of coated eggs. Issa et al [7] reported the same trend for the SPS-based films with TEO. They concluded that by increasing the oil concentrations, the b* value of the film is also increased.…”
Section: Color Parametersmentioning
confidence: 53%
See 2 more Smart Citations
“…These findings indicate that the incorporation of TEO significantly increases the yellowness of coated eggs. Issa et al [7] reported the same trend for the SPS-based films with TEO. They concluded that by increasing the oil concentrations, the b* value of the film is also increased.…”
Section: Color Parametersmentioning
confidence: 53%
“…To initiate gelatinization, the temperature of the solution was raised up to 80 • C and continued for 30 min. Then, glycerol at 2% (w/w, on dry basis of the weight of starch) (Fisher Scientific, Fair Lawn, NJ, USA), was added and mixed for 5 min [7]. In this study, TEO (Thymus vulgaris, New Direction Aromatics, Mississauga, ON, Canada) at various levels including 0.0%, 2.0%, 4.0%, and 6.0% (v/v) was mixed with Tween 80 (Fisher Scientific, Fair Lawn, NJ, USA) and homogenized in the coating solution for 5 min using a laboratory homogenizer (Homogenizer, OMNI International, Kenneswa, GA, USA).…”
Section: Preparation Of Coating Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, there was no significant change in mechanical properties with the inclusion of Cloisite 6A, Cloisite10A, and Cloisite 30B MMTs. Issa et al[51] showed thatFig. 6 XRD spectra of MMT nanoclays and TPS/MMT nanocomposites at different MMT loadings[48] tensile strength, Young's modulus and elongation at break for TPS/MMT nanocomposites were increased by 138.4, 876.0 and 27.2% with the incorporation of 3 wt% MMTs compared with those of TPS.…”
mentioning
confidence: 99%
“…According to Sánchez-Zapata, Viuda-Martos, Fernández-LÓpez, and Pérez-Alvarez (2015), resistant starch helps reduce fat uptake in deep-fried foods, and by the percentage of total starch, sweet potato starch has higher resistant starch concentration than the corn starch. In our previous research, sweet potato starch exhibited promising film-forming ability and good barrier properties (Issa et al, 2018). Thus, replacement of corn starch with sweet potato starch in the batter formulation could be more effective in reducing the fat uptake either in combination with the edible coating or without edible coating.…”
Section: Introductionmentioning
confidence: 98%